STANDING STOCK OF DEMERSAL FISH ASSESSMENT IN SOUTHERN PART OF SOUTH CHINA SEA - Julius A.N Masrikat (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Demersal fish assessment is prerequisite for optimal fishing. In this paper, standing stock of demersal fish in southern part of South China Sea was determined by swept area method. The research was carried out by research vessel SEAFDEC on 18 – 30 June 2005. The catch of fish was obtained from 18 in-situ station use bottom trawl. There were found 154 species and 38 563 individual, respectively. The Leiognathus bindus was dominant species at fishing operation. Catch per unit area (CPUA) was ranged from 62.99 to 748.57 kg km-² and averaged 420.32 kg km-². The overall catch rate ranged 5.6 to 121.97 kg hr-1 and averaged 50.54 kg hr-1. The standing stock of demersal fish in survey area was 124 560 ton.